“EFFECTIVE METHODICAL METHODS OF TEACHING ENGLISH IN GENERAL EDUCATION SCHOOLS” (Ustozlar uchun, 2025)
Today, the younger generation is increasingly interested in learning languages. Therefore, it is necessary to introduce interactive methods into the teaching of English in secondary schools. The article is devoted to the effectiveness of organizing lessons using interactive methods in English lessons in secondary schools.